Aroha: 'Loving' within a statutory and bi-cultural residential environment. Issue 1 (1st December 2016) - Sutherland, Andrew
'Aroha', as the closest Maori language equivalent of the English word 'love', is a concept now ingrained in practice ideals for youth residential work in Aotearoa/New Zealand, as part of a wider social services framework. This has been a purposeful shift over the last quarter century to align with the principle of bi-cultural partnership in social policy, the intentions of which can be traced to early colonial times. 'Aroha' will be explored as an appropriate, cross-cultural residential practice path in the relationship between young people and residential staff. Observations of how this 'love' has been put into practice while maintaining professional standards will be highlighted, alongside discussion of how this might interweave with similar strands of thought from the discipline of social pedagogy.